2019
DOI: 10.1101/769703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining and targeting adaptations to oncogenic KRASG12Cinhibition using quantitative temporal proteomics

Abstract: Covalent inhibitors of the KRAS G12C oncoprotein have recently been developed and are being evaluated in clinical trials. Resistance to targeted therapies is common and likely to limit long-term efficacy of KRAS inhibitors (KRASi). To identify pathways of adaptation to KRASi and to predict drug combinations that circumvent resistance, we used a mass spectrometry-based quantitative temporal proteomics and bioinformatics workflow to profile the temporal proteomic response to KRAS G12C inhibition in pancreatic an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…While the intracellular signaling events modulated by KRAS are currently being evaluated as potential therapeutic targets 14,15 , much less is known about its potential impact on the cell surface. Elucidating how oncogenic KRAS modifies the cell surface proteome (surfaceome) may improve our understanding of its complex mechanism of action, and possibly identify new attractive therapeutic targets.…”
mentioning
confidence: 99%
“…While the intracellular signaling events modulated by KRAS are currently being evaluated as potential therapeutic targets 14,15 , much less is known about its potential impact on the cell surface. Elucidating how oncogenic KRAS modifies the cell surface proteome (surfaceome) may improve our understanding of its complex mechanism of action, and possibly identify new attractive therapeutic targets.…”
mentioning
confidence: 99%
“…Several recent studies have demonstrated that proteomic profiling of oncogene-induced tumorigenesis can aid the design of new treatment strategies, [41][42][43] and two therapeutic hypotheses are raised by our data. The first is that targeting pathways which demonstrate a compensatory upregulation upon FH inactivation (either at the level of protein abundance or cysteine reactivity) may serve to limit adaptation of cancer cells and trigger cell death.…”
Section: Discussionmentioning
confidence: 64%
“…Several recent studies have demonstrated that proteomic profiling of oncogene-induced tumorigenesis can aid the design of new treatment strategies, [38][39][40] and two therapeutic hypotheses are raised by our data. The first is that targeting pathways which demonstrate a compensatory upregulation upon FH inactivation (either at the level of protein abundance or cysteine reactivity) may serve to limit adaptation of cancer cells and trigger cell death.…”
mentioning
confidence: 64%